2017
DOI: 10.1111/epi.13969
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term adherence with psychiatric treatment among patients with psychogenic nonepileptic seizures

Abstract: SummaryWe conducted a prospective cohort study, examining long-term adherence with psychiatric treatment among patients with psychogenic nonepileptic seizures (PNES).Subjects diagnosed with documented PNES were scheduled for 4 psychiatric visits. Survival analysis was performed, and covariates were assessed for association with time to nonadherence using Cox proportional hazard regression analysis. One hundred twenty-three subjects were recruited and followed for up to 17 months. Eighty percent of subjects att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Our overall level of non-attendance at a psychiatry appointment (18.6 %) was at a level that is similar to other studies of referral to mental health services [17], a study in the US of attendance of 123 patients with dissociative seizures referred in the US (20 %) [26] and a previous study of patients with functional neurological disorders referred by neurologists to psychiatrists [19], but higher than levels of non-attendance to general medical services (which tend to run at 5-10 %). This data was obtained in the course of recruiting patients to an RCT reducing the generalisability to general neurological practice.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our overall level of non-attendance at a psychiatry appointment (18.6 %) was at a level that is similar to other studies of referral to mental health services [17], a study in the US of attendance of 123 patients with dissociative seizures referred in the US (20 %) [26] and a previous study of patients with functional neurological disorders referred by neurologists to psychiatrists [19], but higher than levels of non-attendance to general medical services (which tend to run at 5-10 %). This data was obtained in the course of recruiting patients to an RCT reducing the generalisability to general neurological practice.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, it should also be noted that this is only a study of attendance and not of engagement with psychiatric services or of treatment outcome. A study of 123 patients with dissociative seizures scheduled for 4 psychiatric visits found that although 80 % attended the first appointment, 42 % attended the second, 24 % the third and only 14 % the fourth [26]. The authors subsequently demonstrated improved adherence with a randomised controlled trial of motivational interviewing [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in clinical practice, the majority of patients with functional neurological disorders do not complete psychotherapy . Sixty percent of patients with PNES are nonadherent with initial psychotherapy, and 86% drop out of psychiatric follow‐up within 17 months . Risk factors predicting psychotherapy nonadherence among patients with PNES include self‐identified minority status and a history of childhood abuse.…”
Section: Introductionmentioning
confidence: 99%
“…15 Sixty percent of patients with PNES are nonadherent with initial psychotherapy, and 86% drop out of psychiatric follow-up within 17 months. 16,17 Risk factors predicting psychotherapy nonadherence among patients with PNES include selfidentified minority status and a history of childhood abuse. Such nonadherence is associated with worse PNES frequency and quality of life, and increased emergency department (ED) utilization.…”
Section: Introductionmentioning
confidence: 99%